Gestational diabetes mellitus diagnosed at 24 to 28 weeks of gestation in older and obese Women: Is it too late? - Wonjin Kim; Soo Kyung Park; Yoo Lee Kim (PLoS ONE)
Aim/background The prevalence of elderly pregnancy and maternal obesity is increasing worldwide. In old and obese women, metabolic derangement affecting fetal growth might be present earlier than the diagnosis of gestational diabetes mellitus (GDM) or even before pregnancy. We thus investigated whether GDM diagnosed at 24-28 weeks of gestation had already affected fetal abdominal growth and, if so, whether elderly pregnancy and/or maternal obesity aggravate fetal abdominal obesity. Methods We retrospectively reviewed the medical records of 7820 singleton pregnant women who had been universally screened using a 50-g glucose challenge test (GCT) at 24-28 weeks of gestation, and underwent a 3-h 100-g oral glucose tolerance test (OGTT) if GCT were ≥140mg/dl. GDM and normal glucose tolerance (NGT) were diagnosed using the Carpenter-Coustan criteria. Fetal abdominal obesity was investigated by assessing the fetal abdominal overgrowth ratios (FAORs) of the ultrasonographically estimated gestational age (GA) of abdominal circumference per actual GA by the last menstruation period, biparietal diameter or femur length, respectively. Fetal abdominal overgrowth was defined as FAOR ≥ 90th percentile. The subjects were divided into four study groups: group 1 (age < 35 years and pre-pregnancy body mass index [BMI] < 25 kg/m2), group 2 (age < 35 years and ≥ 25), group 3 (age ≥ 35 years and BMI < 25), and group 4 (age ≥ 35 years and ≥ 25). Results The overall prevalence of GDM was 5.1%, with old and obese group 4 exhibiting the highest prevalence (22.4%). FAORs were significantly higher in the fetus of those with GDM than in the NGT subjects. But, in the subgroup analysis, only old and nonobese group 3 and old and obese group 4 with GDM exhibited significantly higher FAORs than the NGT subjects. Also, risk of fetal abdominal overgrowth was increased in group 3 and 4 subjects with GDM but not in young and nonobese group 1 GDM. The risk of fetal abdominal overgrowth significantly increased with maternal age >35 years, pre-pregnancy BMI >20kg/m2, and HbA1c >37.7 mmol/mol (5.6%). In multivariate analyses, maternal age and HbA1c were significantly associated with FAORs. Conclusion GDM diagnosed at 24-28 weeks of gestation already affected fetal abdominal obesity in older and/or obese women, but not in younger and nonobese women. Our data suggest that selective screening and appropriate intervention of GDM earlier than 24-28 weeks of gestation might be necessary for high-risk old and/or obese women.